2007
DOI: 10.1038/sj.leu.2404732
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of Wnt signaling in the pathogenesis of acute myeloid leukemia

Abstract: Wnt signaling plays an important role in stem cell self-renewal and proliferation. Aberrant activation of Wnt signaling and its downstream targets are intimately linked with several types of cancer with colon cancer being the best-studied example. However, recent results also suggest an important role of Wnt signaling in normal as well as leukemic hematopoietic stem cells. Aberrant activation of Wnt signaling and downstream effectors has been demonstrated in acute myeloid leukemia. Here, mutant receptor tyrosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 155 publications
1
75
0
1
Order By: Relevance
“…The dephosphorylated (active) form of GSK3β promotes β-catenin degradation by phosphorylating β-catenin on Ser33/37. 22,23 Consistent with the known activation of β-catenin in AML blasts, 27,32 we found that the levels of nuclear β-catenin were elevated in blasts of a selected AML patient ( Figure 5A). We, therefore, analyzed whether NAMPT or SIRT2 inhibition resulted in increased phosphorylation of β-catenin.…”
Section: Inhibition Of Nampt or Sirtuin 2 Is Associated With β-Catenisupporting
confidence: 81%
See 2 more Smart Citations
“…The dephosphorylated (active) form of GSK3β promotes β-catenin degradation by phosphorylating β-catenin on Ser33/37. 22,23 Consistent with the known activation of β-catenin in AML blasts, 27,32 we found that the levels of nuclear β-catenin were elevated in blasts of a selected AML patient ( Figure 5A). We, therefore, analyzed whether NAMPT or SIRT2 inhibition resulted in increased phosphorylation of β-catenin.…”
Section: Inhibition Of Nampt or Sirtuin 2 Is Associated With β-Catenisupporting
confidence: 81%
“…24 Active nuclear β-catenin has been detected in blasts of myeloid leukemia patients as well as in patients with other hematologic malignancies. [27][28][29][30][31][32][33] Interestingly, we demonstrated that inhibition of SIRT2 or NAMPT resulted in dephosphorylation/activation of GSK3β and subsequent phosphorylation/deactivation of β-catenin, which is the first step in β-catenin degradation. Because inhibition of either SIRT2 or NAMPT induced dephosphorylation/inactivation of AKT, this process is most likely AKT-dependent.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…172 This may occur due to mutations in Flt-3 and chimeric transcription factors such as promyelocytic leukemia gene fused to the Promyelocytic leukemia-retinoic acid receptor-a gene (PML-RARa) and AML-ETO. ITDs of the Flt-3 gene have been detected in leukemia stem cells.…”
Section: Targeting the Leukemic Stem Cellmentioning
confidence: 99%
“…The Wnt-regulated transcription factor, LEF1, is overexpressed in human leukemias, and constitutive activation of LEF1 in mice leads to B-cell lymphoblastic leukemia and acute myeloid leukemia (AML) (Petropoulos et al, 2008). A number of observations suggest that Wnt is important in AML and chronic lymphocytic leukemia (Lu et al, 2004;Mikesch et al, 2007), and abnormal methylation of Wnt pathway components is associated with poor prognosis in ALL patients (Roman-Gomez et al, 2007). The central mediator of the Wnt canonical signaling pathway is the cytosolic protein b-catenin, which clearly has a function in leukemia.…”
Section: Wntmentioning
confidence: 99%